2019
DOI: 10.3390/ma12234013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Granulometry on Thermal and Mechanical Properties of Cement Mortars Containing Expanded Perlite as a Lightweight Aggregate

Abstract: This research aims at clarifying the influence of the granulometry of expanded perlite, on the thermal conductivity, structural strength, density, and water absorption of lightweight mortars. Three original perlite gradations have been obtained and three pairs of twin test mortars have been tested with those gradations. SEM tests have also been run to clarify the interaction, at a microscopic level, between the expanded perlite and the cement grouting. The results indicate that the mere manipulation of the gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Liu et al [31] concluded that the increase in density results in an increase in th values of the thermal conductivity of iron ore sand cement mortar. Subsequent studie [32,33] have confirmed earlier findings. The density at the ages of 28 days and 140 day was assessed, taking into account the two different storage conditions.…”
Section: Densitysupporting
confidence: 64%
“…Liu et al [31] concluded that the increase in density results in an increase in th values of the thermal conductivity of iron ore sand cement mortar. Subsequent studie [32,33] have confirmed earlier findings. The density at the ages of 28 days and 140 day was assessed, taking into account the two different storage conditions.…”
Section: Densitysupporting
confidence: 64%
“…The development of new construction materials, with emphasis on insulation, should be focused on the relation between thermal and mechanical properties of materials, as well as their composition [ 2 ]. Regarding the strict European criteria for the U-value (thermal transmittance) of building envelopes [ 3 ], several studies on the development of thermal enhanced building materials and components have been performed, with a special interest in thermal mortars [ 4 , 5 , 6 , 7 ]. Additionally, the incorporation of nanoparticles in mortars could improve their durability compared to traditional building materials [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perlite is a natural glassy volcanic rock (composition: ≅ 75% of SiO 2 ; ≅ 15% of Al 2 O 3 ) (Ghassabzadeh et al, 2010;Cabuk et al, 2018;Corregidor et al, 2019), termed expanded perlite (EP) after being rapidly heated for 760-1 200°C and consequently expanded up to 20 times its original volume (Alkan and Dogan, 2002;Cabuk et al, 2018;De Oliveira et al, 2019). EP is employed in the construction industry (Papa et al, 2018;Leyton-Vergara et al, 2019;Top et al, 2020;Jiang et al, 2020), composite structure (Rodriguez et al, 2016;Ma et al, 2020;Rathore et al, 2020), agriculture and environmental sectors (Villaseñor et al, 2011;Torab-Mostaedi et al, 2011;Díez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%